FORMULA PENGGANTI METODE KOEFISIEN TAK TENTU - Syofia Deswita; Syamsudhuha '; Agusni ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses an alternative formula to obtain the particular solution of non-homogeneous linear dierential equations of constant coecients, where the nonhomogeneous terms are in the form of a trigonometry, an exponent or a polynomial function, using the multiplication of a polynomial with a complex exponential function. The particular solution obtained is in the form of a polynomial.